THE ROLE OF TECHNOLOGICAL AND PROGRAMMING SKILLS IN A LONG TERM PROCESSES REGARDING SPORT FUNDING - Danijela Bonacin; Dobromir Bonacin; Hadžib Salkić (Sport Scientific And Practical Aspects, 2025)
Regarding management essentiality in today’s world, where the quality and professionalism of managers is considered as a decisive factor that will lead organization into a group of a winners or a group of losers, is an evident reason why we selected high quality managers to be the aim of this research. The goal of this research was to determine correlation between active managers performance on the one hand and usage of technological and programming means on the other hand, in order to define the role of this skills in long term processes regarding sport financing. For this work purposes, we analyzed a sample of 72 high level sport managers from Bosnia and Herzegovina, described with 15 variables from technological, educational, IT, economic, management and sport’s law sectors. Data were gathered through anonymous survey questionnaire based on Likert’s scale. After normalization and basic statistics we conducted canonical correlation analysis in order to determine existence of specific mechanisms within analyzed sample. The results of analysis indicated there are two bipolar factors within mentioned sample. The general definition of first canonical factor would be the way to plan the work which contains two types of performance; planning based on own experience and on the contrary elemental (uncontrollable) work and avoiding technological means. The general definition of the second canonical factor would be the way to provide income which contains two ways of income providing; with active work and modern tools and passive work with no desire to change.